Relationships Between Caregiver Characteristics and Health-Related Quality of Life Among Youth with Spinal Cord Injury - Kelly, Erin H. (Top Spinal Cord Inj Rehabil, 2016)
Background: Past research has found a relationship between the mental health of parental caregivers and their children with spinal cord injury (SCI), but little is known about how other aspects of caregiver health and functioning impact health-related quality of life (HRQOL) of youth. Objective: The purpose of this study was to explore the importance of caregiver mental health, physical health, burden, and problem-solving skills in relation to children's physical and psychosocial HRQOL. Methods: Forty youths with SCI ages 7 to 17 years completed the PedsQL(TM); primary caregivers completed standardized measures of mental and physical health, burden, and problem solving. We evaluated 2 hierarchical linear regression models predicting children's physical and psychosocial HRQOL. Results: The 40 youths were an average of 11.48 years (SD = 3.21), 62.5% were male, and 80% Caucasian. They had been injured an average of 6.90 years (SD = 3.92); 75% had paraplegia, and 61.5% had complete injuries. Most caregivers were mothers (85%), were married (60%), and had at least some college education (87.5%). Univariate analyses revealed that caregiver problem solving alone was related to children's physical HRQOL, and caregiver mental health, burden, and problem solving were related to children's psychosocial HRQOL. Regression analyses controlling for child age and injury level revealed effective caregiver problem solving (P < .01) was significantly related to greater child physical (Model R(2) = 0.440) and psychosocial (Model R(2) = 0.547) HRQOL. Conclusions: Although relationships should be explored longitudinally with larger samples, results indicate caregiver problem solving may be a reasonable target for intervention to improve HRQOL among youth with SCI.